The Phenomenon of Adultification in R. Riggs’s Miss Peregrine’s Home for Peculiar Children - Kmošková Bajerová , Nikola (American & British Studies Annual, 2025)
This article examines the representation of adultification in Ransom Riggs’s Miss Peregrine’s Home for Peculiar Children (2011), focusing on how the narrative positions children within adult roles and responsibilities. Central to the analysis are the concepts of boundary dissolution and parentification, alongside the recurring tropes of the child redeemer and the lost child, and pervasive experiences of trauma and ennui. Through these frameworks, Riggs’s characters are shown inhabiting liminal identities that blur conventional distinctions between childhood and adulthood. Drawing on Kathryn Bond Stockton’s theory of “growing sideways,” the article explores how the peculiar children resist linear models of development and instead inhabit non-normative trajectories of growth shaped by delay, repetition, and queer temporality. By examining these narrative and psychological dimensions, the discussion highlights how Riggs portrays childhood as a space of burden, responsibility, and vulnerability. Ultimately, the article argues that Miss Peregrine’s Home for Peculiar Children challenges conventional frameworks of childhood, offering a complex vision of growth and identity that unsettles developmental norms.